Influence of resistance training load on measures of skeletal muscle hypertrophy and improvements in maximal strength and neuromuscular task performance: A systematic review and meta-analysis. Issue 15 (3rd August 2021) - Refalo, Martin C.; Hamilton, D. Lee; Paval, D. Robert; Gallagher, Iain J.; Feros, Simon A.; Fyfe, Jackson J.
ABSTRACT: This systematic review and meta-analysis determined resistance training (RT) load effects on various muscle hypertrophy, strength, and neuromuscular performance task [e.g., countermovement jump (CMJ)] outcomes. Relevent studies comparing higher-load [>60% 1-repetition maximum (RM) or <15-RM] and lower-load (≤60% 1-RM or ≥ 15-RM) RT were identified, with 45 studies (from 4713 total) included in the meta-analysis. Higher- and lower-load RT induced similar muscle hypertrophy at the whole-body (lean/fat-free mass; [ES (95% CI) = 0.05 (−0.20 to 0.29), P = 0.70]), whole-muscle [ES = 0.06 (−0.11 to 0.24), P = 0.47], and muscle fibre [ES = 0.29 (−0.09 to 0.66), P = 0.13] levels. Higher-load RT further improved 1-RM [ES = 0.34 (0.15 to 0.52), P = 0.0003] and isometric [ES = 0.41 (0.07 to 0.76), P = 0.02] strength. The superiority of higher-load RT on 1-RM strength was greater in younger [ES = 0.34 (0.12 to 0.55), P = 0.002] versus older [ES = 0.20 (−0.00 to 0.41), P = 0.05] participants. Higher- and lower-load RT therefore induce similar muscle hypertrophy (at multiple physiological levels), while higher-load RT elicits superior 1-RM and isometric strength. The influence of RT loads on neuromuscular task performance is however unclear.